Interaction Between Brackish Water Intermittent Infiltration and Cultivated Soil Environment: A Case Study From Arid Piedmont Plain of Northwest China - Leilei, Guo; Zaimin, Wang (Frontiers in Earth Science, 2022)
Brackish groundwater was widely used in arid areas which may cause soil salinization and groundwater environmental declines. To ensure the sustainable development of agriculture in arid areas, brackish water intermittent infiltration experiments were conducted in Southern Xinjiang, Northwest China between Jun. to Sep. 2018, and Hydrus-2D numerical simulation was used to analyze the underground pipe drainage systems. The field experiments were carried out during cotton growth stages after the first fresh water flood infiltration and salt washing. Two control experiments were respectively designed as fresh water (0.68 g / L) and brackish water (1.66 g / L) with water amount of 1.0 Q = 572 mm. Other 8 groups (1.05~1.40Q) were compared to analyze the effect of soil salt leaching by increasing the brackish water amount. The results showed that the soil moisture content was almost less than the field capacity of 0.203 at depth of 0 -60 cm before each infiltration due to roots water uptake and the soil water holding capacity rate was lower than 0.2 after 5 days under 1.20Q - 1.40Q brackish water treatments. Variation of EC1:5 at depth of 0 - 30 cm was less than 0.5 dS/m. Salt mainly accumulated at the depth of 40~60cm whether the water amount was excessive or insufficient even under the fresh water infiltration. The optimal brackish water amount was 1.15Q = 657.8 mm, and the soil total salinity was less than 0.55 dS/m (EC1:5) and reached mild salinization degree. Numerical simulations were used based on the 2018 field experimental results and extended by another 10 years. The soil salt accumulated to 1.10 ~ 2.99 dS/m (EC1:5) at the depth of 40 - 60cm during 0 ~ 30 days. The no salinization area expanded to depth of 40 ~ 45 cm after 120 days and reduced during non - infiltration period due to evaporation effect. The soil salt was gradually leached and less than 0.55 dS/m (EC1:5) after 10 years. The optimized leaching-drainage system could not only provides a low salinity soil condition for cotton growth and realize sustainable cultivation but also greatly protect the soil and groundwater environment.